Profile of Science Literacy of Grade 10 Students Using Computer-Supported Collaborative Learning (CSCL) Model - Januaresty, Wita Wulan; Windyariani, Sistiana; Ratnasari, Jujun (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
This study aims to determine the effect of the CSCL model on science literacy (SL). SL is considered as the abilities to use science knowledge to solve the science problem by utilizing the critical thinking skills. The quasi-experimental with a non-equivalent group design was applied as the research method. Subjects of this research were grade 10 students (N=50).  Different tests were carried out to determine the existence of science literacy. There are 3 aspects of knowledge assessed in SL skills, i.e., content, procedural, and epistemic knowledge. The instruments used was a 15 questions of science literacy consisting of 5 content knowledge, 5 procedural, 5 epistemic questions, and an assessment of interest in SL. The results showed the average of content knowledge of experimental class was 76.92% or in a high category, and control class was 73.33% or in moderate category. The average of procedural knowledge of the experimental class was 66.92% and the control class was 64.99%, or both were moderate. And the average of epistemic knowledge of the experimental class was 64.61% and the control class was 60.99% or both moderate. The assessment of attitudes towards SL aims to give an idea that students have an interest in the components of SL attitudes.